Combined transcriptome and widely targeted metabolome analysis reveals the potential mechanism of HupA biosynthesis and antioxidant activity in Huperzia serrata - Wu, Hao; Shen, Yu; Zou, Fen; Yao, Shiqing; Chen, Yaling; Yang, Huilin; Luo, Xiangdong (Frontiers in Plant Science, 2024)
Introduction Huperzia serrata is a traditional Chinese herb that has gained much attention for its production of Huperzine A (HupA). HupA has shown promise on treating Alzheimer's disease (AD). However, the biosynthetic pathway and molecular mechanism of HupA in H. serrata are still not well understood. Methods Integrated transcriptome and metabolome analysis was performed to reveal the molecular mechanisms related to HupA biosynthesis and antioxidant activity in Huperzia serrata. Results HT (in vitro H. serrata thallus) exhibits higher antioxidant activity and lower cytotoxicity than WH (wild H. serrata). Through hierarchical clustering analysis and qRT-PCR verification, 7 important enzyme genes and 13 transcription factors (TFs) related to HupA biosynthesis were detected. Among them, the average |log2FC| value of CYP (Cytochrome P450) and CAO (Copper amine oxidase) was the largest. Metabolomic analysis identified 12 metabolites involved in the HupA biosynthesis and 29 metabolites related to antioxidant activity. KEGG co-enrichment analysis revealed that tropane, piperidine and pyridine alkaloid biosynthesis were involved in the HupA biosynthesis pathway. Furthermore, the phenylpropanoid, phenylalanine, and flavonoid biosynthesis pathway were found to regulate the antioxidant activity of H. serrata. The study also identified seven important genes related to the regulation of antioxidant activity, including PrAO (primary-amine oxidase). Based on the above joint analysis, the biosynthetic pathway of HupA and potential mechanisms of antioxidant in H. serrata was constructed. Discussion Through differential transcriptome and metabolome analysis, DEGs and DAMs involved in HupA biosynthesis and antioxidant-related were identified, and the potential metabolic pathway related to HupA biosynthesis and antioxidant in Huperzia serrata were constructed. This study would provide valuable insights into the HupA biosynthesis mechanism and the H. serrata thallus medicinal value.